Otokratisasi dan Populisme Otoriter dalam Rezim Demokrasi: Perbandingan antara India, Hongaria, dan Turki - Margiansyah, Defbry (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
Democracy decline undermines optimism for the expansion of worldâ€™s democracy as it occurred in established democracies. The decline from democratic to autocratic regime or â€œautocratizationâ€ is being experienced by India (the worldâ€™s largest democracy), Hungary (the established democracy in the European Union), and Turkey (the influential democracy in the Muslim world). Although they have different views of the main causes of the democracy decline, experts agree that authoritarian tendency driven by autocratic leaders erodes democratic values. The autocratization in the above three democracies is strongly related to â€œauthoritarian populismâ€ adopted by the incumbents and reflected on their antagonistic attitudes towards democracy. This article compares the role of anti-democratic populism in India, Hungary, and Turkey in the process of autocratizing democracies in the last decade. Autocratization in which authoritarian populism plays a significant role occurs through the â€œautocratization stagesâ€ as follows: the politicization of peopleâ€™s disappointment, social polarization based on cultural narratives, weakening of democratic institutions, control of alternative information, and repression of opposition and critics. The article concludes that as seen in the cases of India, Hungary and Turkey, autocratization is highly dependent on the incumbents' skill in exploiting populist rhetoric to legitimize the regime's authoritarian actions.